Dietary Exposure to the Food Contaminant Deoxynivalenol Triggers Colonic Breakdown by Activating the Mitochondrial and the Death Receptor Pathways. Issue 23 (20th October 2021) - Payros, Delphine; Alassane‐Kpembi, Imourana; Laffitte, Joelle; Lencina, Corine; Neves, Manon; Bracarense, Ana Paula; Pinton, Philippe; Ménard, Sandrine; Oswald, Isabelle P.
Abstract : Introduction: The food contamination by mycotoxins is of increasing public health concerns. Deoxynivalenol (DON), a mycotoxin contaminating cereals, has been associated with the exacerbation of inflammatory bowel diseases (IBD), thereby raising the question of its role in the development of IBD. Moreover, the effect of DON on the colon is poorly described. Methods and Results: Wistar rats exposed (1–4 weeks) to low doses of DON (2 or 9 mg kg −1 feed) show microscopic alterations of colonic tissue (dilated lymphatic vessels, luminal debris, and cubic and flattened enterocytes). Ingestion of DON also alters colonic functions by increasing paracellular permeability while reducing the expression of the tight junction proteins and increased apoptosis in colonic tissue. Pro‐apoptotic factors Bax/Bak, cytochrome C, and caspase 9 are upregulated, whereas expression of anti‐apoptotic protein Bcl2 tends to decrease for the mitochondrial pathway. An increased expression of FasR and caspase‐8 is observed for the extrinsic pathway. An increase in the pro‐inflammatory markers TNFα, IL‐17, and myeloperoxidase is also observed. Conclusion: These results indicate that the dietary exposure to low levels of DON in food targets the colon inducing a health‐threatening breakdown of the colonic barrier, highlighting oral exposure to DON as a potential risk factor in triggering IBD. Abstract : Exposure to DON targets the colonic tissue by inducing microscopic alterations and increasing inflammatory markers. By increasing paracellular permeability associated with damaging the tight junction proteins DON induces a health‐threatening breakdown of the colonic barrier. At cellular level, this toxin exposure increases apoptosis through the intrinsic and the extrinsic pathways. In conclusion, food exposure to low level of DON is a risk factor to develop inflammatory bowel diseases.